STRENGTHENING THE IDEOLOGY OF ISLAMIC RELIGIOUS EDUCATION IN THE ERA OF TECHNOLOGICAL DISRUPTION - Ismail, Ismail; Parinduri, Muhammad Abrar; Ibarra, Florante P. (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This study aims to analyze the ideological strengthening of Islamic Religious Education (IRE) in the era of technological disruption within Madrasah Aliyah Negeri (MAN) in Medan City. Amidst rapid digital transformation and the growing influence of globalized information, educational institutions face new challenges in preserving and transmitting religious values to students. Using a qualitative method and a case study approach, this research explores how teachers adapt pedagogical strategies to maintain the relevance of IRE in a digital age. Data were collected through observation, in-depth interviews, and document analysis. The findings reveal that teachers utilize several key strategies to reinforce Islamic ideology, including the clear and contextual delivery of curriculum content, sufficient instructional time, and utilization of available facilities and teaching staff. Furthermore, emphasis is placed on developing students’ critical thinking and reasoning abilities, nurturing civic awareness, promoting tolerance and appreciation for diversity, and aligning learning with students’ interests and talents. These strategies aim to balance religious values with the demands of 21st-century competencies. A novelty contribution of this study is its focus on the intersection between religious education and digital disruption, an area that remains underexplored in existing literature. Additionally, the research highlights structural challenges such as the absence of computer laboratories in several MAN institutions in Medan, which hampers equitable access to digital resources and creates information gaps among students and teachers. The study recommends future research employing mixed methods with broader samples across different regions to provide a more comprehensive understanding of IRE adaptation in the digital era.